AI in the Endoscopy Suite: Does Artificial Intelligence Improve Esophageal Cancer Detection? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
AI in the Endoscopy Suite: Does Artificial Intelligence Improve Esophageal Cancer Detection? Esophageal cancer (EC) remains a formidable challenge in on...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care